Leadership Styles, Quality of Education, and Educational Institution Management: A Systematic Review in the Perspective of Sustainable Education - Sugiyanto, Heri (Journal Corner of Education, Linguistics, and Literature, 2025)
This study aims to uncover the relationship between leadership styles, quality of education, and the management of educational institutions within the context of sustainable education. A systematic literature review of research published between 2014 and 2024 reveals that transformational leadership plays a significant role in enhancing educators' motivation, organisational culture, and creating a conducive learning environment. The quality of education is influenced by the integration of technology, educators' competencies, and innovative teaching approaches. The use of technologies such as augmented reality and online learning platforms significantly improves learning effectiveness; however, challenges such as access inequality in rural areas remain critical issues. Furthermore, data-driven management has been proven to enhance resource efficiency and support informed decision-making. This study concludes that the integration of leadership styles, education quality, and sustainability-based management is essential to achieving adaptive, inclusive, and innovative education. These findings provide practical contributions in designing sustainable education strategies and supporting the achievement of the Sustainable Development Goals (SDGs). With a comprehensive approach, this research offers both theoretical and practical insights for educational institution leaders in addressing the challenges of globalisation and digitalisation.